Specious Bedfellows: Ethnicity, Animality, and the Intimacy of Slaughter in Moby-Dick ... - Schuller, Kyla C. (Wiley Periodicals, 2010)
“Specious Bedfellows” argues that Moby-Dick is an exploration of the deeply affective relationships pre-industrial whaling ironically nurtured between whales and whalers through the very intimacy of the hunt. Melville’s portrayal of whaling animates a key trope of sentimentalism in its manifestations in mid-century political economy, research in natural history, and domestic ideology – the feeling animal – in order to reveal the self-serving relations at the heart of the discourse of sympathy. He represents both whales and whalers as affective, emotional subjects deserving of empathy from the emerging middle classes who had veracious appetites for sperm whale oil. His animals reveal the ways in which sentimental feeling, now widely recognized as the ideology of the antebellum middle class, both depended on using animal bodies for their own purposes and was increasingly dependent on the exploitative, unsympathetic labor practices facilitating the accumulation of capital. In Melville’s acerbic critique, ...